PERAN GERAKAN PEMUDA ANSOR (GP ANSOR) DALAM MENUMBUHKAN NASIONALISME DI KALANGAN PEMUDA KELURAHAN KARANGROTO KECAMATAN GENUK KOTA SEMARANG - Safira, Pratin Nurdian (Unnes Civic Education Journal, 2017)
The purpose of this study was to determine the role of Ansor Youth Movement (GP Ansor) in growing nationalism among the youth village Karangroto Genuk District of the city, which is a constraint factor Ansor Youth Movement (GP Ansor) in growing nationalism among the youth village Karangroto Genuk District of Semarang City , This study used qualitative methods to answer the problem formulation. Karangroto research location in the Village District of Genuk Semarang. The technique of collecting data using interviews and documentation. The results obtained from this study is the role of Ansor Youth Movement (GP Ansor) in growing nationalism among the youth village Karangroto Genuk District of Semarang City through existing activities in the work program. a) Basic Cadre Training (PKD), b) Basic Training Education (Diklatsar, constraints Ansor Youth Movement (GP Ansor) in growing nationalism among the youth village Karangroto Genuk Subdistrict Semarang City can be classified into two parts, namely, a) internal constraints include busy work , family problems and personal fulfillment, and b) external constraints include funding, other organizations, and enthusiastic youth. Researcher proposed suggestions are as follows, suggestions for the organization Ansor Youth Movement (GP Ansor) Twig Karangroto to increase activities that will encourage the growth of nationalism such as holding national seminars, then to administrators Ansor Youth Movement (GP Ansor) Twig Karangroto expected to improve the administration of document redaction organization, advice for young people to join the organization Karangroto Karangroto and more enthusiastic people to follow events or community activities in Karangroto, suggestions for the village Karangroto to better support the activities of civil society organizations in Karangroto by helping round of funding.